On the formation of thermal barrier coatings by magnetron sputtering - Gennady V. Kachalin; Konstantin S. Medvedev; Aleksey F. Mednikov; Olga S. Zilova; Aleksandr B. Tkhabisimov; Dmitriy I. Ilyukhin; Vladislav A. Kasyanenko (Frontier Materials & Technologies)
The use of magnetron sputtering systems with extended uncooled targets will allow developing industrial import-substituting technologies for the formation of thermal barrier coatings, based on zirconium oxide doped with rare earth metal oxides to solve urgent problems of gas turbine construction. This paper presents the results of comparing the technology for producing thermal barrier coatings by magnetron sputtering, with two types of extended targets made of Zr–8%Y alloy – a widely used cooled target and an uncooled extended target, of a magnetron sputtering system developed by the authors. This paper gives a comparison of the results of mass-spectrometric studies of the hysteresis of the oxygen partial pressure inherent in the technology for producing oxide films; the influence of the target type on the coating growth rate; studies of the structure of thermal barrier coatings using the scanning electron microscopy method; and the elemental composition of coatings based on zirconium dioxide partially stabilised with yttrium oxide – YSZ. It has been experimentally found that increasing the temperature of the magnetron sputtering system target, allows decreasing the loop width of the characteristic hysteresis of the oxygen partial pressure dependence on its flow rate by 2 times. The obtained dependencies allowed determining the range of oxygen flow rates at various magnetron discharge powers, at which the work can be performed with stable and sustainable process control, without the risk of falling into hysteresis. The conducted metallographic studies showed a characteristic developed porous dendritic structure of the ceramic layer, which is necessary to reduce the thermal conductivity coefficient of the thermal barrier coating. It has been revealed that the use of an uncooled target allows increasing the deposition rate of the thermal barrier coating by more than 10 times compared to the deposition rate for a cooled target. The obtained results demonstrate the possibility of using the magnetron sputtering technology of an extended uncooled target to form a ceramic layer of thermal barrier coatings.